Analisis Pembiayaan Multijasa Dengan Akad Ijarah - Dariana Dariana; Wawan Ismanto (JPS (Jurnal Perbankan Syariah), 2020)
The purpose of this research was to determine the practice of multi-service financing with the Ijarah contract at the Sharia People's Financing Bank Berkah Dana Fadhlillah Air Tiris Kampar Regency. This research uses qualitative methods with data collection methods in the form of observation, interviews and literature study. One of the financing products offered by the Sharia People's Financing Bank Berkah Dana Fadhlillah is multi-service financing with an Ijarah contract that aims to obtain service fees (ujrah) in the financing. The multi-service Ijarah Financing at the Sharia People's Financing Bank Berkah Dana Fadhlillah is in accordance with sharia and refers to the fatwa stipulated by the Indonesian Ulema Council No. 09 of 2000 concerning Ijarah and fatwa of the Indonesian Ulema Council No. 44 of 2004 concerning multi-service financing. The multi-service Ijarah financing mechanism at the Sharia People's Financing Bank Berkah Dana Fadhlillah is not complicated but the Sharia People's Financing Bank continues to apply caution in providing financing. That this is one of the factors of people's interest in Ijarah products which are decreasing and not developing every year.